Creative Practices Around the Production of Cork - Reaes Pinto, Paula (2017)
Cork, as a natural product provided by the bark of the cork oak tree, is an important staple of the Portuguese economy and important to Portuguese culture. It is a sustainable product with a positive ecological footprint, from harvesting to industrial production, with the advantage of creating a local economic model through regional labour activity and distribution. Within the balance between nature-human-economy to create a sustainable system, cork production in Portugal represents a human and social dimension. By focusing on that dimension and by creating an awareness of the cultural and social impact of the activity and by re-appraising the meaning of the material within the culture, the study reframes a consideration of the actual place of labour and production. The human, geophysical, historical, social, economic, ecological and cultural aspects of the place are observed as regards their relation to work or labour in that physical space. A pilot study is being developed in the village of Azaruja in the district of Évora, Portugal. In this small locality, cork is very important in terms of the relationships between the physical subsistence of their residents and the local natural resources, because it structures the place in its cultural, social and economical dimensions. This paper outlines the theoretical foundations, the process and the outcomes of the participatory ecodesign project titled Creative Practices Around the Production of Cork which was initiated by a Portuguese artist/design researcher and developed further through the collaboration with the other two authors, one a Portuguese visual artist/researcher and the other a Turkish fashion designer/theorist. The investigation focuses on questions that expand the notion of place for artists and designers, filtered through the lenses of manual labourers in order to understand their physical, social, cultural and economic relationship with the environment. To create the process of interaction with the place and the people, a creative collaborative dynamic is developed between the authors with their range of artistic sensibilities and the local population. To adopt a holistic notion of sustainability and cultural identity a process of investigation is designated to: (1) analyse, test and interpret - through the dissemination of life stories, visual representation of the place and the creation of cork objects - the importance of culture related to the labour activity of a local natural resource that determines and structures the region; (2) to give public recognition to those involved, taking into account their sense of belonging to the place and in order to show the value of their sustainable labour activities related to local natural resources; (3) to contribute to the knowledge of the place and to its dynamism through an aesthetic approach to labour activities. With reference to fields of knowledge such as anthropology, the social arts and sustainable design, a practice-based research is conducted with collaborative and participatory design methods to create an open model of interaction which involves local people in the realization of the project. Outcomes of this research will be presented in the paper as a survey analysis with theoretical conclusions.